UNVEILING DETERMINANTS OF TECHNOLOGY ADOPTION IN FOOD SUPPLY CHAIN: A STUDY OF INDONESIA’S SMES - Fauziana, Diyah Ratna (Universitas Pakuan, 2025)
ABSTRACTThis study aims to investigate the adoption of technology by small and medium enterprises in the supply chain sector in Indonesia, namely by identifying the determinants of technology adoption and providing recommendations to improve technology adoption. This study uses a qualitative method, which begins with a literature review, and the results are verified through interviews with nine sources of food supply chain actors. The study results produce several determinants of technology adoption in SMEs: business strategy, business pressure, perceptions of benefits, and management support. The intervention recommendations for this study are programs to improve employee knowledge and skills, increase collaboration, and develop leadership in SMEs. This study contributes practically as input for government programs or other stakeholders to improve technology adoption in SMEs, making them more focused and effective. Government programs that facilitate collaboration between supply chain actors and develop knowledge and skills in human resources in SMEs will have a positive impact.ABSTRAKPenelitian ini bertujuan untuk menginvestigasi adopsi teknologi oleh usaha kecil menengah di sektor supply chain di Indonesia, yaitu dengan mengidentifikasi faktor penentu adopsi teknologi dan menentukan rekomendasi untuk meningkatkan adopsi teknologi. Penelitian ini menggunakan metode kualitatif, yang diawali kajian literatur dan diverifikasi hasilnya melalui wawancara dengan sembilan orang narasumber pelaku rantai pasok pangan. Hasil studi menghasilkan beberapa determinan adopsi teknologi pada UKM, yaitu strategi bisnis, tekanan dunia bisnis, persepsi atas manfaat dan dukungan manajemen. Rekomendasi intervensi studi ini adalah program peningkatan pengetahuan dan kemampuan karyawan, peningkatan kolaborasi, dan pengembangan kepemimpinan pada UKM. Studi ini berkontribusi praktis sebagai masukan untuk program pemerintah atau pemangku kepentingan lainnya untuk meningkatkan adopsi teknologi pada UKM, sehingga lebih terfokus dan efektif. Program pemerintah dalam memfasilitasi kolaborasi antar aktor rantai pasok dan pengembangan pengetahuan dan kemampuan pada sumber daya manusia di UKM akan memberikan dampak yang positif.